The suitability assessment of groundwater recharge by leakage of the Yongding River - Xinyi CAO; Yuanzheng ZHAI; Muzi LI; Chengzhong PAN; Fuxin ZHENG; Hong LU; Xuelian XIA; Yanguo TENG; Jinsheng WANG (Shuiwen dizhi gongcheng dizhi, 2022)
Due to the effect of climate changes and human activities, groundwater over-exploitation and aquifer depletion have become global issues of concern. Artificial recharge of groundwater through a river has been paid more attention among a variety of artificial intervention measures. It is found that not all rivers or river reaches are suitable for artificial recharge of groundwater owing to the limitations of recharge potential by infiltration and storage capacity of the vadose zone. At present, there is still a lack of widely accepted suitability assessment methods. In this study, the Yongding River in the Beijing Plain section and the underlying aquifer are taken as the study area and the case study is carried out. Moreover, the measured data are used to verify the results. The suitability assessment model (LMBGITSC model) constructed by the index system method includes eight indexes: land use types of riverbed, sediment types of riverbed, channel width, channel topographic slope, medium types of the vadose zone, thickness of the vadose zone, specific yield of the vadose zone and horizontal permeability of the vadose zone. The results show that the suitability of groundwater recharge in the Yongding River changes from good degree to medium degree along the river flow direction (except the reaches carried out anti-seepage engineering), presenting a "step-type" evolution law. The proposed method is of good applicability and can also provide reference for similar regions.